Primary and secondary somatic embryogenesis in Jatropha curcas L. From leaf transverse thin cell layers - Loan, Nguyen Thi Kim; Giap, Do Dang; Tuan, Tran Trong; Hien, Nguyen Thi Thanh; Huy, Nguyen Phuc; Du, Thai Xuan; Nhut, Duong Tan (Vietnam Journal of Biotechnology, 2018)
An efficient method for plant regeneration in Jatropha curcas L. via primary and secondary somatic embryogenesis culture from ex vitro leaves of 6-month-old plants was presented in this study. Leaves were cut into transverse thin cell layers (tTCLs) and cultured on MS medium supplemented with kinetin (KIN) at 0.5, 1.0, 1.5, and 2.0 mg/l in combination with indole-3-butyric acid (IBA) at 0.1, 0.5, and 1.0 mg/l or 2,4-dichlorophenoxyacetic acid (2,4-D) at 1.0, 1.5 and 2.0 mg/l . The highest embryogenic callus formation rate (89.3%) was obtained on medium supplemented with 1.0 mg/l KIN and 1.5 mg/l 2,4-D. The calli were selected for the study of primary somatic embryogenesis on MS medium containing 2,4-D (0.01, 0.03, 0.05, and 0.07 mg/l) or KIN (0.5, 1.0, 1.5, and 2.0 mg/l). The highest primary somatic embryos formation rate (76.67%) was achieved on MS medium supplemented with 1.0 mg/l KIN. The primary embryos were cultured on medium supplemented with KIN (0.1, 0.5, 1.0, 1.5, and 2.0 mg/l) combined with 0.2 mg/l indole-3-butyric acid (IBA) or 0.05 mg/l 2,4-D. The combination of 1.5 mg/l KIN and 0.05 mg/l 2,4-D was suitable for secondary embryos formation. Embryos proliferated rapidly, and the highest number of secondary embryos (77.5 embryos) wasobtained from a single primary embryos inoculated. Results also showed that the addition of proline (0.75 g/l) or spermidine (0.15 mM) to the culture medium increased the number of secondary embryos considerably. The fully developed plantlets exhibiting healthy roots and shoots were obtained when somatic embryos were sub-cultured onto B5 medium containing 1.5 mg/l IBA